Hybrid subcarrier multiplexing Flexible Cross Correlation (FCC) Ocoma fiber-wireless access network - Junita, Mohd. Nordin Dr. (Universiti Malaysia Perlis (UniMAP), 2014)
Received a Gold medal in 25th International Invention, Innovation & Technology Exhibition (ITEX'14), 8th-10th May at Kuala Lumpur Convention Centre.